DOES COVID-19 PANDEMIC INCREASE THE USE OF CASHLESS BANKING DIGITAL SERVICES? THE CASE OF INDONESIA - Dyah Anggraeni; Ersa Wahyuni; Hamzah Ritchi (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2023)
Restrictions in covid-19 pandemic have increased the need for digital services in all sectors including the banking industry. The purpose of this study is to analyze whether there has been a changes in Indonesian banks services before and during the covid-19 pandemic. This study uses a quantitative method and non-parametric Wilcoxon tests, using secondary data taken from 180 Annual Reports from 45 banks listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period as samples. The results shows that there has been significant change in cashless mobile banking transactions during the pandemic. This research adds new insights into the latest developments and evaluation topic for banking companies.